La troménie de Locronan, la fête de Lughnasa et le calendrier celtique - Donatien Laurent (La Bretagne Linguistique, 1987)
The unique character of the troménie of Locronan, this sacred procession in the direction of the sun’s march, which every year on the second Sunday of July, claims to reproduce the daily ascent of the founding saint, the Irishman Ronan, to his mountain, has long been mentioned. Every six years, the procession expands in a new dimension both in space (12 kilometres instead of 6) and in time (8 full days, from the second to the third Sunday of July) to follow, step by step, the penitential journey that the saint made every Sunday around his hermitage. The aim of this paper is to present the results of a work that postulates the extension of the ancient Celtic festival of Lug in the troménie of Locronan.